Strategi Membangun Digital Marketplace Untuk Industri Baja Terintegrasi Melalui Pendekatan Enterprise Architecture - Budi Chandra (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The era of digital disruption has resulted in business instability in various sectors, including the steel industry sector. Many companies are thinking of out-of-the-box ideas to survive the impact of digital disruption, and some companies are even more successful in advancing their business. The steel industry business faces serious challenges in carrying out digital transformation, including in the areas of supply chain, sales, production, inventory, delivery and financial transactions. It is not impossible if the steel industry business can be integrated through an online marketplace, with tons of material weight and involving billions of transactions. In this study, the business model design is described using the Business Model Canvas (BMC) and the elements involved are integrated using the Archimet Model Tools. The results of the modeling by integrating business elements, application elements, data elements and technology are expected that the company can build an effective, efficient marketplace and create a good customer experience as a value proposition. Based on interviews with experienced experts in the steel industry and marketplace business, this study focuses on at least 4 (four) sources of income, namely: sales of steel products, seller member subscription fees, sharing revenue logistics tracking, sharing revenue payment gateways.